2014
DOI: 10.24839/2164-8204.jn19.4.173
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Childhood Family Environment and Adult Sexual Offending in a Sample of Sexual Offenders

Abstract: www.psichi.org psichijournal@psichi.org ® ® ABOUT PSI CHI Psi Chi is the International Honor So ci ety in Psychology, found ed in 1929 for the pur pos es of encouraging, stim u lat ing, and maintaining ex cel lence in schol ar ship, and advancing the sci ence of psy chol ogy. Mem ber ship is open to gradu ate and under gradu ate men and women who are mak ing the study of psy chol ogy one of their major interests and who meet the min i mum qual i fi ca tions. Psi Chi is a member of the As so cia tion of Col leg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Participants with ID were also less likely to be raised in a two-parent home than participants without ID. A previous study that utilized the present sample found that individuals who were raised in a two-parent home were less likely to use physical violence during the index offense (O’Toole & Jeglic, 2014).…”
Section: Discussionmentioning
confidence: 75%
“…Participants with ID were also less likely to be raised in a two-parent home than participants without ID. A previous study that utilized the present sample found that individuals who were raised in a two-parent home were less likely to use physical violence during the index offense (O’Toole & Jeglic, 2014).…”
Section: Discussionmentioning
confidence: 75%
“…In addition, compared with perpetrators of nonsexual assaults, sex offenders exhibit more personality disorders such as schizoid, obsessive-compulsive characteristics, and an avoidant personality (Fazel, Hope, Donnell, & Jacoby, 2002). Moreover, a negative personal and family history (Moroge et al, 2014; O’Toole & Jeglic, 2014) are thought to affect the individual’s development (development of an insecure anxious attachment, disorders of behavioral or emotional capacities of regulation, disorders of capacities of mentalization) and are factors that contribute to a vulnerability to psychopathological disorders (Schneck, Bowers, & Turkson, 2012). Another factor concerns socioaffective and relationship abilities ( relationship and contextual dimension ) and, in particular, impairment in emotional processes.…”
Section: Introductionmentioning
confidence: 99%